Odd hours - Koontz, Dean R. (Dean Ray), 1945- (New York : Bantam Books, 2008)
Haunted by dreams of a powerful red tide, Odd Thomas, accompanied by two otherworldly sidekicks, his dog Boo and the Chairman of the Board, is drawn to a small California coastal town, where nothing is at it appears and where he confronts overwhelming and sinister forces out to stop his quest.
Keywords: Cooks -- Fiction; Mediums -- Fiction; Occult fiction; Horror fiction